The Translation Techniques in Fouad Al-Takerli’s "Al-Raji’ Al-Ba’iid" in Catherine Cobham’s Translation "The Long Way Back " - Abd AlSahib, Ass.Lecture Maysoon Mohsen (Thi Qar Arts Journal, 2022)
This study aims at distinguishing the translation techniques and analyzing the changes resulted from using those techniques in Fuad al-Takerli’s “Al-Raji’ Al-Ba’iid” translated by Catherin Cobham. Certain techniques may cause different kinds of changes whether syntactic like for example, changing a verb to a noun or semantic like changing a proper name to an attribute , while other techniques may not cause any change .It is a fact that some techniques may be used more frequently than others .The narrative text having unique linguistic characteristics must be translated using different styles and techniques .These techniques can be used as words and sentences to facilitate the difficulty of translating culturally specific problematic items. Usually a translator faces many difficulties in making accurate translation .This paper analyses the techniques of translation and determine their functions and the distinguished features in narrative in order to present accurate description to the resulted syntactic and semantic changes .In “The Long Way Back” , where all elements of narrative text are used , literal and free translation are adopted to keep the value of the original text . By employing certain techniques and procedures in the target language, a translator will attempt to shift the meanings using different linguistic devices in work recreation. This paper sheds light on the different techniques used in translating this kind of text which is composed of different styles .Through the study , it is concluded that most of translation techniques are used .Most of the resulting changes are semantic ,while the syntactic changes are merely changes in parts of speech .